Dissoì lógoi § 5: contextualización, traducción e interpretación - Gardella, Mariana (Revista Archai, 2019)
The aim of this paper is to analyze Dialex. § 5 in order to show that the author not only uses eristical arguments, but he also offers a solution to them. First, I present some general remarks about the date of composition, authorship, and structure of the treatise so as to appreciate the singularity of the fifth paragraph. Then, I offer a complete translation of Dialex. § 5 and I point out the similarities between the arguments presented there and some eristic paradoxes discussed in Plato’s Euthydemus and Aristotle’s Sophistical Refutations. Finally, I analyze Dialex. § 5. 15 and I propose an interpretation of the argument based on the philosophical context in which it was formulated.